Strategies for the Development of Hospitality SMEs in Kabul, Afghanistan / Shabir Ahmad Ab. Saleem and Naree Weerakit - Ab. Saleem, Shabir Ahmad; Weerakit, Naree (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
This paper aims to investigate the obstacles impeding the development of hospitality small and medium sized enterprises (HSMEs) in Kabul, Afghanistan and to propose proper strategies supporting their development. Data was collected through questionnaires distributed to 90 HSMEs (hotels, guesthouses, restaurants, coffee shops and wedding halls) which totalled up to 36% of the population. The findings indicated that HSMEs face several internal and external obstacles such as lack of basic infrastructure, security concerns, the high cost of raw materials, high tax etc. In this regard, specific development strategies and policies have been proposed for both HSMEs and the government. Some of the key strategies pertain to: setting up a strategic plan, human resources training and development and adoption of information and communication technology (ICT) etc. Meanwhile the government needs to take into its policy consideration, the development of basic infrastructure, reduction of taxes, giving more priority to the tourism and hospitality industry and the establishment of funding and advisory bodies.